Is Marketing Limited to Promotional Activities? The Concept of Marketing: A Concise Review of the Literature - Waheed, Abdul; Yang, Jianhua; Ahmed, Zahid; Rafique, Kalsoom; Ashfaq, Muhammad (Asian Development Policy Review, 2017)
This paper endeavors to describe the core concept of marketing and marketing management with the means of existing studies. However, it is occasionally observed that business students narrow the concept of marketing and limit to advertising or promotional activities. However, the contribution of this paper is to enrich student’s knowledge and attempts to diminish misconception among young students. Consequently, the study is compiled with the help of comprehensive literature review through research papers, books, official web sources, and some interviews of seniors Professors in the discipline of marketing management. Therefore, the current study endeavored to highlight the concept of marketing and represented that marketing is not limited to advertising activities. Despite, it is a complete strategic process which creates value for the customers and raises the long-term relationship with them. While promoting the product through distinct advertising mediums is an essential element of the marketing management process. Furthermore, the present study provides a structure to marketing students in order to grasp the fundamentals associated with marketing philosophy.